Introduction and Psychometric Validation of the Resilience and Strain Questionnaire (ResQ-Care)— A Scale on the Ratio of Informal Caregivers' Resilience and Stress Factors - Wuttke-Linnemann, Alexandra; Palm, Svenja; Scholz, Lea; Geschke, Katharina; Fellgiebel, Andreas (Frontiers in Psychiatry, 2021)
Background: Informal caregivers are a particularly vulnerable population at risk for adverse health outcomes. Likewise, there are many scales available assessing individual caregiver burden and stress. Recently, resilience in caregivers gained increasing interest and scales started to assess resilience factors as well. Drawing on a homeostatic model, we developed a scale assessing both caregivers’ stress and resilience factors. We propose four scales, two covering stress and two covering resilience factors, in addition to a sociodemographic basic scale. Based on the stress:resilience ratio, the individual risk of adverse health outcomes and suggestions for interventions can be derived. Methods: A total of 291 informal caregivers filled in the ResQ-Care as part of a survey study conducted during the second wave of COVID-19 pandemic in Germany. Exploratory factor analysis was performed. Validity analyses were examined by correlations with the Brief Resilience Scale (BRS), the Perceived Stress Scale (PSS-4) and the Geriatric Depression Scale (GDS-15). Results: The data fitted our proposed four-factor solution well, explaining 43.3% of the variance. Reliability of each scale was at least acceptable with Cronbach’s α ≥ .67 and MacDonald’s ω ≥ .68 for all scales. The two strain scales weighed more than the resilience scales and explained 65.7% of the variance. Convergent and discriminant validity was confirmed for the BRS and PSS-4, whereas the GDS-15 correlation pattern was counterintuitive. Conclusion: The factor structure of the ResQ-Care scale was confirmed, with good indications of reliability and validity. Inconsistent correlations of the scales with the GDS-15 might be due to a reduced validity of GDS-15 assessment during the COVID-19 lockdown.